[Delta]-catenin: implications in prostate cancer progression - Nopparat, Jongdee (East Carolina University, 2014)
Prostate cancer (PCa) is the most commonly diagnosed cancer and the second most common cause of cancer death among men in the US. Due to the advances in research, the ability to detect and cure PCa has improved and led to significant reductions in PCa patients' mortality. Therefore, determining and understanding specific molecular mechanisms involved in PCa progression is a pivotal step towards the potentially better and more accurate diagnosis and intervention of PCa in the future. [Delta]-catenin is a unique armadillo (Arm) domain containing protein in that it is neural specific and primarily expressed in the brain. However, [delta]-catenin alterations have been implicated in pathogenesis ranging from neuronal deficits, genetic disorders, to cancers. In particular, [delta]-catenin expression is shown to increase in primary human prostatic adenocarcinomas corresponding with PCa progression. Although overexpressed [delta]-catenin in PCa has been reported over a decade ago, few studies have been undertaken to identify how [delta]-catenin promotes PCa progression and what other significant molecules are relevant to its expression. Studies presented in this dissertation explore the effects of a truncated variant of [delta]-catenin involved in promoting PCa using both in vitro PCa culture systems and in vivo mouse models of PCa. Additionally, we aim to test the hypothesis that [delta]-catenin mutations promote PCa progression by interacting with multiple cancer-specific pathways including β-catenin/LEF-1-mediated transcription and HIF-1α. Information presented in this dissertation demonstrates that ectopic [delta]-catenin gene is susceptible to mutagenesis when overexpressed in PCa cells, CWR22Rv-1 and PC-3, leading to sequence disruptions predicting functional alterations. It is shown that PCa cells overexpressing mutant [delta]-catenin increase β-catenin translocation to the nucleus and HIF-1α; expression when cultured under glucose deprived condition. These results suggest that [delta]-catenin mutations provide a survival advantage upon overgrowth and glucose deprivation over the control cells. Furthermore, we demonstrate that [delta]-catenin mutations promote tumor development in mouse prostate with probasin promoter (ARR₂PB)-driven, prostate specific expression of Myc oncogene. Additional investigations indicate that [delta]-catenin mutations in Myc transgenic mice not only promote β-catenin expression leading to dramatically elevated Myc expression but HIF-1α; is also increased in a [delta]-catenin gene-dosage dependent manner. Overall, we reveal that the introduction β-catenin mutations is an important step in metabolic adaptation by modulating β-catenin and HIF-1α; signaling in order to magnify its tumor promoting effect
Keywords: Biology, Molecular; [Delta]-catenin; Glucose deprivation; Prostate--Cancer; Somatic mutations; Transgenic mouse models; δ-catenin; Molecular biology; Prostatic Neoplasms--diagnosis; Catenins--metabolism; Adenocarcinomas--diagnosis